Impact of ground-level ozone on Mediterranean forest ecosystems health - Jakovljević, Tamara; Lovreškov, Lucija; Jelić, Goran; Anav, Alessandro; Popa, Ionel; Fornasier, Maria Francesca; Proietti, Chiara; Limić, Ivan; Butorac, Lukrecija; Vitale, Marcello; De Marco, Alessandra (The Science of the total environment, 2021)
Given the high ozone concentrations observed in the Mediterranean region during summer, it is crucial to extend our knowledge on the potential ozone impacts on forest health with in situ studies, especially to protect typical endemic forests of the Mediterranean basin. This study is focused on ozone measurements and exposures over the Eastern Adriatic coast and on the calculation of different O3 metrics, i.e., accumulated exposure AOT40 (AOT40dir, AOT40ICP, AOT40pheno) and stomatal O3 fluxes with an hourly threshold of uptake (Y) to represent the detoxification capacity of trees (PODY, with Y = 0, 1, 2 nmol O3 m−2 s−1) used for forest protection. Finally, we provide an assessment of the relationships between the forest response indicators and environmental variables. Passive ozone measurements and monitoring of forest health indicators, namely growth and crown defoliation, were performed for Quercus ilex, Quercus pubescens, Pinus halepensis, and Pinus nigra forests. Results showed that, for all the analysed species, ozone levels were close to reached the upper plausibility limits for passive monitoring of air quality at forest sites (100 ppb), with the highest values found on P. halepensis in the summer period. O3 metrics based on exposure were found to be higher in pine plots than in oak plots, while the highest values of uptake-based metrics were found on P. nigra. Regarding relationships between environmental variables and forest-health response indicators, the crown defoliation was significantly correlated with the soil water content at various depth while the tree growth was correlated with the different O3 metrics. The most important predictors affecting tree growth of Q. pubescens and Q. ilex were AOT40pheno and AOT40dir and POD0 for P. nigra. [Display omitted] •Ozone metrics from passive O3 measurements in Mediterranean forests were estimated.•Higher ozone exposure doses (AOT40) were observed in P. nigra and P. halepensis plot, while higher ozone fluxes (PODY) in P. nigra.•Relationships between environmental parameters and forest health response indicators were assessed.•Defoliation was significantly correlated with soil water content at various depths.•The most important predictors affecting tree growth were AOT40 and POD0.